2019
DOI: 10.1007/s00198-019-05105-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of milk powder intervention on bone mineral density and indicators related to bone metabolism in Chinese adolescents

Abstract: SummaryThe study is to determine the effects of milk powder on bone density and metabolism in healthy adolescents. Vitamin D and calcium supplements increased IGF-1 but did not affect bone mineralization or turnover. Higher vitamin D in combination with sufficient calcium supplementation in such populations requires attention.IntroductionBoth calcium and vitamin D play an important role in bone mineralization in adolescents.MethodsIn this one and a half-year randomized controlled trial, 232 participants (aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Participants in seventeen studies were only females ( 5 , 18 33 ) and in two studies were only males ( 34 , 35 ). Eight studies addressed children and adolescents ( 36 – 43 ). The mean age of subjects varied from 2 yr ( 42 ) to 84 years ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in seventeen studies were only females ( 5 , 18 33 ) and in two studies were only males ( 34 , 35 ). Eight studies addressed children and adolescents ( 36 – 43 ). The mean age of subjects varied from 2 yr ( 42 ) to 84 years ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…are different from the other studies. These two studies were in children (< 15-year-old) ( 37 , 43 ), while the other studies were in participants older than 50-year-old. Sensitivity analysis indicated that by omitting these studies the pooled estimate was still in favor of intervention (Difference in means=9.38, P -value=0.008, CI 95%: 2.48 to 16.29).…”
Section: Resultsmentioning
confidence: 99%
“…9-12 22-60 Table 1 shows the baseline characteristics of the included studies. Of the 43 RCTs, 20 used dietary sources of calcium, 11 12 22 23 25 27-29 40 43-46 48 49 53 54 56 60 and 23 used calcium supplements (including calcium, calcium citrate malate and calcium phosphate). 9 10 24 26 30-39 41 42 47 50-52 55 57 59 The median baseline dietary calcium intake was 714 mg/day; the duration of calcium supplementation intervention did not exceed 2 years in most trials (38/43); and the dose of calcium intervention did not exceed 1000 mg/day in most trials (38/43).…”
Section: Resultsmentioning
confidence: 99%
“…9 10 However, several clinical trials have concluded that calcium supplementation may not be associated with calculated bone mass or strength. 11 12 Narrative reviews have also concluded that calcium supplementation may have small nonprogressive effects on BMD or BMC. 13 14 To summarize the studies above, there have been considerable debates about whether calcium supplementation has effects on bone health among young people.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials have shown positive effects of calcium supplementation on BMD or BMC in children ( Lloyd et al, 1993 ; Khadilkar et al, 2012 ). However, several clinical trials have concluded that calcium supplementation may not be associated with calculated bone mass or strength ( Lu et al, 2019 ; Vogel et al, 2017 ). Narrative reviews have also concluded that calcium supplementation may have small nonprogressive effects on BMD or BMC ( Winzenberg et al, 2006 ; Huncharek et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%